The mortality risk after myocardial infraction in migrants compared with natives: a systematic review and meta-analysis - Zhu, Lei; Huang, Bao-tao; Chen, Mao (Frontiers in Cardiovascular Medicine, 2023)
Background and Objective The evidence on the risk of mortality after myocardial infarction (MI) among migrants compared with natives is mixed and limited. The aim of this study is to assess the mortality risk after MI in migrants compared to natives. Methods This study protocol is registered with PROSPERO, number CRD42022350876. We searched the Medline and Embase databases, without time and language constraints, for cohort studies that reported the risk of mortality after myocardial infarction in migrants compared to natives. The migration status is confirmed by country of birth. Two reviewers separately screened searched studies according to selection criteria, extracted data and assessed data quality using the Newcastle‒Ottawa Scale (NOS) and risk of bias of included studies. Pooled estimates of adjusted and unadjusted mortality after MI were calculated separately using a random-effects model, and subgroup analysis was performed by region of origin and follow-up time. Result A total of 6 studies were enrolled, including 34,835 migrants and 284,629 natives. The pooled adjusted all-cause mortality of migrants after MI was worse than that of natives (OR, 1.24; 95% CI, 1.10–1.39; I2=83.1%), while the the pooled unadjusted mortality of migrants after MI was not worse than that of natives (OR, 1.11; 95% CI, 0.69-1.79; I2=99.3%). In subgroup analyses, adjusted 5-10 years mortality (3 studies) was higher in the migrant population (OR, 1.27; 95% CI, 1.12–1.45; I2=86.8%),while adjusted 30 days (4 studies) and 1-3 years (3 studies) mortality were not significantly different between the two groups. Migrants from Europe (4 studies) (OR, 1.34; 95% CI, 1.16–1.55; I2=39%), Africa (3 studies) (OR, 1.50; 95% CI, 01.31–1.72; I2=0%), and Latin America (2 studies) (OR, 1.44; 95% CI, 1.30–1.60; I2=0%) had significantly higher rates of post-MI mortality than natives, with the exception of migrants of Asian origin (4 studies) (OR, 1.20; 95% CI, 0.99–1.46; I2=72.7%). Conclusions Migrants face a higher risk of mortality after MI in the long term compared to natives. Further research is needed to confirm our conclusions, and more attention should be paid to the cardiovascular health of migrants.